Valores de futuros engenheiros ambientais sobre o meio ambiente - Tonin, Ivone Borges da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Environmental issues are among the topics that have received great attention and aroused the concern of contemporary society, in view of the need for environmental planning according to various imbalances caused by the development of modern society. Examining the work in the Environmental area, one can observe that still remain, in society in general, visions whose concepts are accompanied by a sense of control, supervision or inaccessible scenarios and unattainable to the individual. This perspective is influenced possibly by the view that the professionals themselves convey. This thesis aims to analyze the future environmental engineers design the environment. The analysis is focused on the prevailing values and the level of social perspective of decentralization (inspired by Kohlberg) obtained. With regard to the method, was performed a case study for which they were selected Environmental Engineering Academic course. The instrument used was a questionnaire consisting of four items. The sample comprised 39.2% of male participants and 60.8% female, the mean age was 23.5 years, the motivation for the choice of the course was predominantly related to interest and vocation and areas of intended action were related to water resources, water treatment and / or waste and environmental preservation and recovery of degraded areas. The economic classification showed that prevail students of economy class B (62.4%). The specific questions showed that 95.2% of respondents said they were involved in the preservation of the environment and 32% have already developed or developing work in environmental education. The analysis of Likert Scale showed that most of the academics is geared to a system of ecocentric values, scientific, emotional and ethical / social and environmental, and does not agree with anthropocentric and instrumental values. In the first vignette is observed that the value of the studied group ecocentric prevailed. In the second...

As questões ambientais estão entre os temas que têm merecido grande atenção e despertado a preocupação da sociedade contemporânea, tendo em vista a necessidade de um planejamento ambiental em função de vários desequilíbrios causados pelo desenvolvimento da sociedade moderna. Examinando-se os trabalhos na área Ambiental, pode-se observar que ainda permanecem, na sociedade em geral, visões cujos conceitos são acompanhados de uma percepção de controle, fiscalização ou cenários inacessíveis e inatingíveis ao indivíduo. Essa perspectiva é influenciada, possivelmente, pela visão que os próprios profissionais transmitem. A presente dissertação visa a analisar como os futuros engenheiros ambientais concebem o meio ambiente do ponto de vista ético. A análise é focada nos valores predominantes e no nível de descentralização de perspectiva social (inspirados em Kohlberg) obtidos. No que se refere ao método, foi realizado um estudo de caso para o qual foram selecionados acadêmicos do curso de Engenharia Ambiental. O instrumento utilizado foi um questionário composto por quatro itens. A amostra contou com 39,2% de participantes de sexo masculino e 60,8% do sexo feminino, a idade foi em média de 23,5 anos, a motivação para a escolha do curso foi predominante relacionada a interesse e vocação e as áreas de atuação pretendidas foram ligadas a recursos hídricos, tratamento de águas e/ou resíduos e preservação ambiental e recuperação de áreas degradadas. A classificação econômica mostrou que prevalecem alunos da classe econômica B (62,4%). As questões específicas mostraram que 95,2% dos entrevistados se declararam envolvidos na preservação do meio ambiente e 32% já desenvolveram ou desenvolvem trabalhos em educação ambiental. A análise da Escala Likert evidenciou que grande parte dos acadêmicos é voltada a um sistema de valores ecocêntricos, científicos, afetivos e éticos/socioambientais, e...
Keywords: Meio ambiente; Ética ambiental; Engenharia ambiental; Valores; Estudantes de engenharia; Environment